2013
DOI: 10.1016/j.mam.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Folate and thiamine transporters mediated by facilitative carriers (SLC19A1-3 and SLC46A1) and folate receptors

Abstract: The reduced folate carrier (RFC,SLC19A1), thiamine transporter-1 (ThTr1,SLC19A2) and thiamine transporter-2 (ThTr2,SLC19A3) evolved from the same family of solute carriers. SLC19A1 transports folates but not thiamine. SLC19A2 and SLC19A3 transport thiamine but not folates. SLC19A1 and SLC19A2 deliver their substrates to systemic tissues; SLC19A3 mediates intestinal thiamine absorption. The proton-coupled folate transporter (PCFT,SLC46A1) is the mechanism by which folates are absorbed across the apical-brush-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
155
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 99 publications
(140 reference statements)
1
155
0
1
Order By: Relevance
“…data in [126]). Another example here is provided by Ray and colleagues [272,273], who noted that a variety of molecules, including Janus kinase (JAK) inhibitors such as fedratinib, were transported by and/or were inhibitors of two of the three main thiamine transporters (SLC19 family [274]), thereby inducing Wernicke's encephalopathy (due to thiamine deficiency). A kind of QSAR model (in this case a pharmacophore model) suggested that 2,4-diaminopyrimidine-containing compounds can in fact adopt a conformation matching several key features of thiamine.…”
Section: Figure 5 Unsupervised and Supervised Learning Methods In Chmentioning
confidence: 99%
“…data in [126]). Another example here is provided by Ray and colleagues [272,273], who noted that a variety of molecules, including Janus kinase (JAK) inhibitors such as fedratinib, were transported by and/or were inhibitors of two of the three main thiamine transporters (SLC19 family [274]), thereby inducing Wernicke's encephalopathy (due to thiamine deficiency). A kind of QSAR model (in this case a pharmacophore model) suggested that 2,4-diaminopyrimidine-containing compounds can in fact adopt a conformation matching several key features of thiamine.…”
Section: Figure 5 Unsupervised and Supervised Learning Methods In Chmentioning
confidence: 99%
“…LV, into the cells (27). Below pH 7, the transport of folates by SLC19A1/RFC-1 decreases dramatically and is mainly accomplished by SLC46A1/PCFT.…”
Section: Ggh) and Folate Metabolism (Aldh1l1 Aldh1l2 Amt Atic Ftcmentioning
confidence: 96%
“…S2B). In the same context and as the human thiamine transporter belongs to the folate transporter family (Zhao and Goldman, 2013), we also tested folate, but it did not compete for TDP transport (Supplemental Fig. S2B).…”
Section: Kinetics Of Put3-facilitated Thiamine Transportmentioning
confidence: 99%